The Effect of Service Quality and Trust on High Click Priority Customer Loyalty, Profit Saving at Bank Sinarmas - Aisyah Siregar (Jurnal Mantik, 2021)
This study aims to determine how the influence of service quality and customer trust on customer loyalty with high cliff priority to save at Bank SinarmasTebingTinggi. The research method used is descriptive and verification methods. While the data used is primary data. To find out whether the independent variable has a significant effect on the dependent variable, multiple linear regression methods are used. The results show that Service Quality and Customer Trust affect the loyalty of TebingTinggi priority customers. This can be seen from the significance value of 0.000 or much more. small compared to the significance value used in the study which is five percent (5%) in addition to the t-count value of Service Quality is (10.121) greater than the t-table value (1.984) and the t-count value of Customer Trust is (1.258) more smaller than the t-table value (1984). While the regression equation obtained by Customer Loyalty is Y = 2.487 + 0.624 X1 + 0.142 X2. the adjusted R square value is 0.584 or 58.4%. This shows that the Service Quality Variable (X1) and Customer Trust Variable (X2) can explain the Customer Loyalty Variable (Y) of 58.4%, the remaining 41.6% (100% - 58.4%) is explained by other variables outside the research model. this. In other words, Service Quality and Customer Trust affect the Loyalty of Tebing Tinggi Priority Customers to save at Bank Sinarmas Tebing Tinggi.